Membentuk Peserta Didik Mengakui dan Menghargai Keberagaman Ras dan Adat Istiadat - Martina Labora Nainggolan; Agriva J. Pandiangan; Yusniarti Situmorang; Hisardo Sitorus (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses the importance of pluralism and multiculturalism in building a peaceful and harmonious society amid the cultural, religious, and ethnic diversity in Indonesia. Pluralism emphasizes the importance of mutual respect and valuing differences, while multiculturalism asserts that every culture has an equal status and deserves appreciation. These two concepts play a strategic role in strengthening national unity, preventing social conflicts, and fostering tolerance between religious groups and cultural communities in Indonesia. In the context of the existing diversity, the implementation of pluralism and multiculturalism not only strengthens the unity of the nation but also creates an inclusive and just society. Education that integrates these values is key in shaping a generation that appreciates differences and upholds harmony. This article uses a theoretical approach and social analysis to emphasize that pluralism and multiculturalism are the main foundations for the realization of a civilized society that respects differences and lives in unity. Therefore, these values need to be applied in every aspect of social life, education, and public policy.